2023
DOI: 10.20944/preprints202309.0213.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nitric Oxide as a Determinant of Human Longevity and Health Span

Burkhard Poeggeler,
Kumar Sandeep Singh,
Kumar Sambamurti
et al.

Abstract: The master molecular regulators and mechanisms determining longevity and health span include nitric oxide (NO) and superoxide anion radicals (SOR). L-arginine, the NO synthase (NOS) substrate, can restore a healthy ratio between the dangerous SOR and the protective NO radical to promote healthy aging. Antioxidant supplementation orchestrates protection against oxidative stress and damage—L-arginine and antioxidants such as vitamin C increase NO production and bioavailability. Uncoupling of NO generation with t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…Food rich in L-arginine and antioxidants can exert potent anti-aging effects that increase health and fitness. Biomatrix precision supplementation uses nutrients that target the decisive metabolic pathways [40][41][42][43][44][45][46][47][48]. These are the arginine and tryptophan pathways, and they have to be rerouted [49][50][51][52][53][54][55][56][57][58][59][60].…”
Section: Chrononutrition and Synchronisationmentioning
confidence: 99%
See 4 more Smart Citations
“…Food rich in L-arginine and antioxidants can exert potent anti-aging effects that increase health and fitness. Biomatrix precision supplementation uses nutrients that target the decisive metabolic pathways [40][41][42][43][44][45][46][47][48]. These are the arginine and tryptophan pathways, and they have to be rerouted [49][50][51][52][53][54][55][56][57][58][59][60].…”
Section: Chrononutrition and Synchronisationmentioning
confidence: 99%
“…Recent research has confirmed the decisive roles of these metabolic pathways in regulating and determining human health [40][41][42]. Exploring new avenues that enable active living and healthy aging by preserving our fitness throughout our entire lifetime is the ultimate aim and goal of ongoing research in the field [43][44][45][46][47][48]. The upregulation of NO bioavailability can prevent premature aging and neurodegeneration characterized by cognitive decline [49][50][51][52][53][54][55][56][57].…”
Section: Determinants Of Life and Health Spanmentioning
confidence: 99%
See 3 more Smart Citations